Penyuluhan pengaruh penambangan emas ilegal terhadap lingkungan dan kesehatan masyarakat di Desa Sentajo Kuansing - Thamrin Thamrin; Zulfan Saam; Nofrizal Nofrizal; Rahman Karnila (PELANTAR PRESS, 2021)
Unlicensed Gold Mining (PETI) is widely found in this country. One of them is PETI in Kuansing District, Riau Province, Indonesia. The impact of this mining affects several aspects, such as landscape, economy, social, culture as well as public health. In this case, the Unri team provided counseling to the community in Sentajo Kuansing on July 1, 2020, and monitored several areas that were affected by the damage to the land caused. At the beginning, before and after the counseling was carried out, the mining community and those affected, especially the polluted river water, were given a questionnaire. So that the results of the counseling were obtained whether the participants could understand what was presented by the resource persons.